Supervisory control and data acquisition system for solar panel based on Internet of things (IoT) - Raihan Alfiansyah, Muhammad; Ta ali; Yuhendri, Muldi; Sardi, Juli (Journal of Industrial Automation and Electrical Engineering, 2024)
Supervisory control and data acquisition (SCADA) system on IoT-based solar power plant using HMI, PC, and Smartphone interfaces. HMI uses KTP 700 Comfrot, Siemens S7-1200 PLC connected to the internet via Ngrok, using Siemens TIA Portal V17. The purpose of monitoring the realtime state of the PLTS such as the condition of batteries, solar panels, inverters and loads used and maintaining from troubleshooting. This research designs hardware and software devices to develop a SCADA system. including PLC, HMI, PC, battery, SCC, inverter, solar panel and sensor devices and other actuators are arranged in such a way. software design is carried out in TIA Portal to program PLC and HMI, Node Red as an implementation of the internet of things. in the research it can be concluded that the application of ngrok on the localhost system is very easy, because it does not require a homebase to connect with an external network. and the output of solar panels is not always monitored by the temperature and solar radiation of the SCADA system on solar power plants based on the internet of things. the implementation of the internet of things uses Node Red and Ngrok software as a link between localhost and external networks. So the internet of things in this test can be controlled and monitored remotely with a cacatan must always be connected to the internet. Monitoring, control and data access systems work well